Neonatal Cyanosis: Diagnostic and Management Challenges. (19th December 2010) - Izraelit, A.; Ten, V.; Krishnamurthy, G.; Ratner, V.
Abstract : Neonatal central cyanosis is always a sign of serious pathological processes and may involve diverse organs and impose a significant diagnostic and therapeutic challenge. Here, we report an unusual presentation of Ebstein's anomaly, a rare congenital heart malformation, as the cause of central cyanosis in a one-week-old full-term infant. Initiation of PEG1 therapy in neonates with Ebstein's anomaly always needs a very careful consideration because of a high risk for the development of a "circular shunt" leading to severe deterioration of multiple organs perfusion.